Impact of Galectin-Receptor Interactions on Liver Pathology During the Erythrocytic Stage of Plasmodium berghei Malaria - Wu, Yifan; Huang, Shiguang; Xiao, Siyu; He, Jian; Lu, Fangli (Frontiers in Immunology, 2021)
Hepatopathy is frequently observed in patients with severe malaria but its pathogenesis remains unclear. Galectins are evolutionarily conserved glycan-binding proteins with pleiotropic roles in innate and adaptive immune responses, and exhibit pivotal roles during Plasmodium spp. infection. Here, we analyzed the impact of blockage of galectin-receptor interactions by treatment with alpha (α)-lactose on liver immunopathology during the erythrocytic stage of malaria in mice infected with Plasmodium berghei ANKA (PbANKA). Our results found that compared with PbANKA-infected mice, blockage of galectin-receptor interactions decreased host survival rate, exacerbated liver pathology, increased peripheral blood parasitaemia and tissue parasite burden, increased the numbers of CD68+ macrophages and apoptotic cells in the livers on days 5 and 7 post infection (p.i.), as well as increased mRNA expression levels of galectin-9 (Gal-9) and its receptor, the T cell immunoglobulin domain and mucin domain protein 3 (Tim-3), interferon (IFN)α, IFNγ, and the triggering receptor expressed on myeloid cells (TREM)-1 in the livers or spleens of PbANKA-infected mice on day 7 p.i. Observed by transmission electron microscopy, the peritoneal macrophages isolated from malarial mice with α-lactose treatment had more pseudopodia than those from malarial mice. Measured by using quantitative real-time reverse transcription-polymerase chain reaction assays, the mRNA expression levels of Gal-9, IFNα, IFNβ, IFNγ, and TREM-1 were increased in the peritoneal macrophages isolated from malarial mice with α-lactose treatment in comparison of those from malarial mice. Furthermore, significant positive correlations existed between the mRNA levels of Gal-9 and Tim-3/IFNγ/TREM-1 in both the livers and the peritoneal macrophages, and between Gal-9 and Tim-3/TREM-1 in the spleens of malarial mice; significant positive correlations existed between the mRNA levels of Gal-9 and IFNγ in the livers and between Gal-9 and IFNα in the peritoneal macrophages from malarial mice treated with α-lactose. Our data suggest a potential role of galectin-receptor interactions in limiting liver inflammatory response and parasite proliferation by down-regulating the expressions of IFNα, IFNγ, and TREM-1 induced by PbANKA infection.